High genetic connectivity and Population Expansion of Scomber japonicus in the Northern Humboldt Current System revealed by mitochondrial D-Loop region sequences - Barahona Padilla, Sergio Paolo (2017)
The Chub mackerel (Teleostei: Scombridae) supports an important fishery in the Southeastern Pacific, however, its population genetics status is currently unknown. In the present study the population genetic structure, gene flow and historical demography of this resource in the Northern Humboldt Current System were examined. Samples were collected between 2103 and 2014 from three fishing points off the Peruvian coast (Paita, Ventanilla and Ilo) and analyzed using mitochondrial D-Loop region sequences. A total of 29 polymorphic sites and 35 haplotypes were found in 72 individuals. Moderate haplotype diversity and very low levels of nucleotide diversity were found. Analysis of gene flow showed high levels of connectivity among sampling areas. Analysis of molecular variance, pairwise comparisons and genetic differentiation tests confirmed the lack of genetic structuring. These analyses suggest that analyzed sampling locations can be considered as a single gene pool. Migratory behavior, the high dispersal potential of early stages and the lack of oceanographic barriers can explain its genetic homogeneity along the Peruvian sea. The historical demography was also examined. Neutrality testing, mismatch distribution and Bayesian skyline plot suggested a population expansion scenario that took place during the Late Pleistocene. This study provides novel information about population genetics of the chub mackerel from the Southeastern Pacific.